Professionals in Distress: Issues, Syndromes, and Solutions in Psychology. 1986
DOI: 10.1037/10056-005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse among psychologists.

Abstract: Models of Alcoholismhe term alcoholism has idiosyncratic connotations and usually means what the user chooses it to mean. Much disagreement and controversy abound regarding what constitutes alcoholism. On the one hand, no one T quarrels with the fact that alcohol abuse, be it a disease, a bad habit, or a culturally induced behavior pattern, carries with it a multitude of medical, familial, social, and work problems that dwarf those of any other so-called disease in our society (Vaillant, 1983). On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…These include examinations, financial difficulties, time pressure and work overload. Several American studies of psychologists have been reported (Boyer, 1984 ;Laliotis & Grayson, 1985 ;Thoreson & Skorina, 1986). Overall, these studies suggest that the prevalence of distress and impairment among psychologists is at least as high and often higher than in the general non-professional population.…”
mentioning
confidence: 97%
“…These include examinations, financial difficulties, time pressure and work overload. Several American studies of psychologists have been reported (Boyer, 1984 ;Laliotis & Grayson, 1985 ;Thoreson & Skorina, 1986). Overall, these studies suggest that the prevalence of distress and impairment among psychologists is at least as high and often higher than in the general non-professional population.…”
mentioning
confidence: 97%
“…Office staff may also act as buffers; they too become enablers. Counselors who use alcohol and drugs tend to zealously protect their privacy by working alone and limiting professional contacts, so that many see clients in their offices without review by their peers (Thoreson & Skorina, 1986). McCrady (1989), when discussing alcohol and other drug use disorders, described "a range of symptoms [which] characterize these problems, including loss of control, continued use of the substance despite problems as a result of use, tolerance and withdrawal, and hazardous use of the substance" (p. 339).…”
Section: Drug and Alcohol Abusementioning
confidence: 99%
“…The psychology literature uses the term distressed in conjunction with impairment (Good, Thoreson, & Shaughnessy, 1995;Kilburg, 1986;Kilburg, Nathan, & Thoreson, 1986;McCrady, 1989;Sherman, 1996;Sherman & Thelen, 1998;Thoreson, Miller, & Krauskopf, 1989;Thoreson & Skorina, 1986). The medical field suggests that ''any physical, emotional or educational deficiency that interferes with the quality of .…”
mentioning
confidence: 97%